Low-velocity impact response of lightweight green and cellulosic composite sandwich - Nicholas Hoo Tien, Kuan; Mohamad Zaki, Hassan; M.Y.M., Zuhri (CRC PRESS. Taylor & Francis Group, 2025)
Man-made vitreous fibres are typically carcinogenic and may impair health by promoting the risk of cancer with extended exposure. Green growth has recently been widely featured from an environmental angle to create green markets and promote low carbon mobility whilst managing waste holistically. One of the solutions to reducing waste in the environment and helping climate change is by preventing waste at the source during manufacturing. The study of green material can help cope with the depletion of non-eco-friendly resources and reduce the usage of synthetic materials. Many researchers have aimed to characterise the performance of fibre-reinforced polymer composites based on natural fibre, and the low-velocity impact response has been investigated. Many different types of plant fibres with very complex structures may enable fine-tuning of the final composite structure geometry. The characteristics of the composite may also be changed by adding green elements from various plant parts.